2018
DOI: 10.21500/20112084.3239
|View full text |Cite
|
Sign up to set email alerts
|

Funciones ejecutivas y alta capacidad intelectual en niños en edad escolar: ¿se superponen por completo?

Abstract: Abstract:Objective: To analyze the relationship between the dimensions of the executive function and intellectual capacity in children with high academic performance. Method: an analytical, observational, prospective study with a non-random sample of 104 children between 7 and 11 years of age, belonging to educational institutions in Medellín, Colombia, divided into groups according to the measure of Total Intellectual Capacity (TIC): 1. Those with an average TIC of between 85-115. 2. Children with higher IC o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 34 publications
0
5
0
1
Order By: Relevance
“…Se ha abordado la relación entre inteligencia y FE en poblaciones de diferentes franjas de edad, por ejemplo, Maureira (2018) tras una revisión de 14 estudios empíricos realizados en sujetos sanos, reportó que en el 93 % de dichos estudios se presentó algún grado de relación o predictibilidad entre los constructos en cuestión; de este modo en escolares, adolescentes, universitarios, adultos y gemelos se exponen relaciones variables entre CI y FE; entre CI y planificación, inhibición y MT. Resultados diferentes se reportan en otros estudios en los que no se encontró asociación estadísticamente significativa entre la inteligencia y las FE (Montoya-Arenas et al, 2018).…”
Section: Discussionunclassified
“…Se ha abordado la relación entre inteligencia y FE en poblaciones de diferentes franjas de edad, por ejemplo, Maureira (2018) tras una revisión de 14 estudios empíricos realizados en sujetos sanos, reportó que en el 93 % de dichos estudios se presentó algún grado de relación o predictibilidad entre los constructos en cuestión; de este modo en escolares, adolescentes, universitarios, adultos y gemelos se exponen relaciones variables entre CI y FE; entre CI y planificación, inhibición y MT. Resultados diferentes se reportan en otros estudios en los que no se encontró asociación estadísticamente significativa entre la inteligencia y las FE (Montoya-Arenas et al, 2018).…”
Section: Discussionunclassified
“…Some authors have shown IGC outperform in some domains of attention, such as tonic alerting (Shi et al., 2013) and executive control (Duan et al., 2009; Liu et al., 2011a, 2011b). However, these empirical findings have not been observed in others studies (Montoya‐Arenas et al., 2018; Viana‐Sáenz et al., 2020). The results of this current study provide additional information on the characteristics of the attentional abilities in IGC.…”
Section: Discussionmentioning
confidence: 56%
“…IGC show higher performances in executive control than nongifted children (Duan et al, 2009;Johnson et al, 2003;Oppong et al, 2019). However, others authors have not observed this high performance in executive control in IGC (Montoya-Arenas et al, 2018;Viana-Sáenz et al, 2020, for a meta-analysis). There is thus a discrepancy in empirical findings on the particularity of executive control in IGC.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…There was a lack of assessing other aspects of cognitive function, such as executive function and attention. Although recent intelligence measurements claimed that they could measure executive function or attention, 32 these neuropsychological functions did not fully report in plasticizer exposure articles. These cognitive functions involve different concepts and do not always have similar outcomes.…”
Section: Discussionmentioning
confidence: 99%